CONCEPTS AND PRACTICE OF EDUCATIONAL ADMINISTRATION IN THE DIGITAL ERA - Azhari, Aristo; Gito Dinata; Racela, Tavania; Hidayatullah, Rully (Cahaya Ilmu Bangsa, 2024)
A digital-based education management platform simplifies administrative processes, from storing student data to real-time academic reporting.Furthermore the concept of education administration in the digital era requires the development of the digital capabilities of stakeholders, especially teaching staff.This article also highlights the challenges we face, such as the digital divide and data security, as well as opportunities that can be optimized to improve the quality of education services.Thus, education administration in the digital era not only changes the way education is managed, but also has a significant impact on the effectiveness and efficiency of the entire education system